PRACTICE LOVING TEACHERS: ANALYSIS OF THE DESIGN Freire AN EXPERIENCE REPORT IN SCHOOL HALL PATRICK MARCHON PORTAL-RJ (2006 - 2012) (Fiep Bulletin - online, 2014)
The aim of this study was to analyze, from the perspective of Freire to this loveliness in teaching practices, a qualitative approach and method of procedure based on the reporting experience of the researcher. The period (2006 - 2012), the school unit EMPatrick Marchon Portal. It was concluded that the practice must be loving acquired and developed by teachers, a dialogical relationship and humble, whose main purpose is to ensure that students have opportunities for social transformation and emancipation. The exercise of the loveliness of teaching practice is a practice to combat social inequalities present within and outside of schools, in the search for genuine liberation and ideological.
Keywords: teaching practice; loveliness; education